Discontinuation of anti-seizure therapy in epilepsy patients - O. A. Milovanova; M. B. Mironov; E. A. Sandu (Эпилепсия и пароксизмальные состояния)
Currently, among one of the most important issues in epileptology is discontinuation of anti-seizure therapy in patients with epilepsy. The article presents contemporary approaches to solving the problem of discontinuation of antiepileptic drugs (AEDs) in patients with epilepsy based on assessing Russian and foreign publications, as well as our clinical experience. A comprehensive analysis of high-priority medical sources on AED discontinuation was carried out, including recommendations proposed by the Italian League Against Epilepsy (2013), practical recommendations for adults and children released by the American Academy of Neurology (2021) currently referenced on the official International League Against Epilepsy website, as well as recommendations of the Russian League Against Epilepsy (2022). A fundamentally crucial point in all the recommendations presented above is the lack of strict time frames, and that all provisions can be discussed with a patient and patient’s relatives. It is emphasized that a high quality of life of a patient with epilepsy is achieved only in the absence of epileptic seizures. In this regard, it seems extremely important to apply an individual approach to AED discontinuation, depending on preferences specified by a patient and patient’ family. All aspects related to AED discontinuation should be discussed by neurologists (epileptologists) in collaboration with lawyers, patient family members and various community representatives, not forgetting about the medical-social, medical-legal and ethical issues that arise upon AED discontinuation as well as decision-making on removing the diagnosis of epilepsy.